2013
DOI: 10.1016/j.fitote.2012.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced absorption of boswellic acids by a lecithin delivery form (Phytosome®) of Boswellia extract

Abstract: The anti-inflammatory potential of Boswellia serrata gum resin extracts has been demonstrated in vitro and in animal studies as well as in pilot clinical trials. However, pharmacokinetic studies have evidenced low systemic absorption of boswellic acids (BAs), especially of KBA and AKBA, in rodents and humans. This observation has provided a rationale to improve the formulation of Boswellia extract. We present here the results of a murine comparative bioavailability study of Casperome™, a soy lecithin formulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(61 citation statements)
references
References 18 publications
0
57
0
Order By: Relevance
“…Incorporating bioactive phytoconstituents into phospholipid molecules is reported to improve the aqueous solubility, the membrane permeability, and hence the systemic absorption and bioavailability of the active phytoconstituents. Such complexes are appropriately called phytosomes, herbosomes, or naturosomes (3,4). Studies have reported success in improving the pharmacological profiles of several bioactive phytoconstituents using drugphospholipid complexation technique (5-9).…”
Section: Introductionmentioning
confidence: 99%
“…Incorporating bioactive phytoconstituents into phospholipid molecules is reported to improve the aqueous solubility, the membrane permeability, and hence the systemic absorption and bioavailability of the active phytoconstituents. Such complexes are appropriately called phytosomes, herbosomes, or naturosomes (3,4). Studies have reported success in improving the pharmacological profiles of several bioactive phytoconstituents using drugphospholipid complexation technique (5-9).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, poor absorption and tissue penetration of BAs have been speculated. It was reported that a lecithin delivery form significantly improved absorption of BAs (Hüsch et al, 2013). To our knowledge, efficacy of FRA was significantly enhanced after processed.…”
Section: Introductionmentioning
confidence: 63%
“…The study showed significantly higher plasma levels (up to 7-fold for KBA, and 3-fold for βBA quantified as area under the plasma concentration time curve, AUC last ) for weight equivalent and equimolar oral administration of Casperome™ compared to the non-formulated extract 69 .…”
mentioning
confidence: 89%